HUBUNGAN USIA IBU, JUMLAH PARITAS, DAN MASA GESTASI BAYI DENGAN KLASIFIKASI BAYI BERAT BADAN LAHIR RENDAH DI RSPAD GATOT SOEBROTO TAHUN 2022 - Elvira Aulia Zahra (2023)
ABSTRACT Low birth weight (LBW) refers to babies weighing less than 2,500 grams at birth. LBW is an important issue in public health. The incidence rate of LBW is still high globally, especially in developing countries. There are several risk factors that contribute to the classification of LBW, including social demographic factors, obstetric factors, medical conditions present in the mother, environmental factors, pregnancy age less than 37 weeks, maternal habits, and infections. The study aims to identify the relationship between mother's age, the number of previous births (parity), and the age of pregnancy with the LBW classification. Method: This research uses a quantitative analytical observational approach with a cross-sectional research design. Data collection is done using the total sampling technique. The sample of the study consisted of all mothers who gave birth to babies with LBW in the RSPAD Gatot Soebroto during the period 1 January to 31 December 2022. The study involved 117 patients who gave birth to BBLR babies as the subject of the study. The results: the majority of 20-35 years old 88 people (74.6%), multipares 56 people (47.5%), pre-term groups 84 people (71.2%), low birthweight 64 people (54.2%). There is a significant relationship between maternal age (p=0.006) and parity (p =0.002) with BBLR classification. No significant relationship was found between gestation time (p=0.821) and LBW classification. There is a significant relationship between the age and parity of the mother with the LBW classification, but there is no significant link between the gestation period of the baby with the LBW class. Discussion: The greater the age of the mother >35 years at the time of pregnancy, the higher the risk of having a child with LBW. The more parity the mother has, the greater the likelihood of having LBW. Keywoard : Age, Gestational age, Low birth weight, Parity.